A Christmas Carol - Tavner, Gill (Nigeria, 2007)
Miserable old miser Ebenezer Scrooge hates Christmas. Can somebody so selfish, so harsh and so horribly lonely ever change his ways? In one terrifying night, poor Scrooge is haunted by four ghosts. Why do they show him visions of his past? Why do they show him other people enjoying Christmas? Why do they show him the deaths of a young boy and of a miserable old master?...
Keywords: Christmas Carol; Classic; Juvenile Fiction